Self and Other in Schizophrenia: A Cognitive Neuroscience Perspective - Fisher, Melissa (Am J Psychiatry, 2008)
OBJECTIVE: Recent basic science data indicate that, in healthy individuals, self-referential processing and social cognition rely on common neural substrates. We assessed self-referential source memory and social cognition in a large sample of schizophrenia outpatients and healthy comparison subjects in order to test and contrast how these critical processes are associated in the two groups. METHODS: Ninety-one schizophrenia outpatients and 30 healthy comparison subjects were assessed on measures of basic social cognition and source memory for previously learned word items: self-generated, externally-presented, and new words. Partial correlations and multiple regression analysis tested the association of social cognition measures to source memory performance, and the contributions of source memory and general cognitive abilities to a social cognition composite score. RESULTS: Schizophrenia subjects demonstrated significantly lower source memory for self-generated items (self-referential source memory), but intact external source memory. In both groups, self-referential source memory and social cognition showed strong correlations. When the effects of general cognitive abilities were controlled, these correlations were attenuated in the schizophrenia subjects. Regression analysis revealed discrepancies between groups in the cognitive functions contributing to social cognition performance. CONCLUSIONS: Impaired self-referential source memory represents a unique cognitive deficit in schizophrenia. Further, the strong association between self-referential source memory and social cognition seen in healthy subjects is reduced in schizophrenia and is moderated by general cognitive abilities. Impairments in the neurocognitive system that underlies both self-referential and social cognition provide a parsimonious explanation for the disturbances in the sense of “self” and “other” that characterize schizophrenia.